WADAH HIBURAN, INOVASI DAN EDUKASI TATABOGA TAHU TEMPE DI SEMANAN - Gabriella Gabriella; Diah Anggraini (Jurusan Arsitektur dan Perencanaan, 2020)
Even thought the level of consumption of tahu tempe is very high, and Indonesia is currently the largest tahu and tempe producer country in the world, but the tahu tempe craftsmen still experiencing problems with fluctuating soybean raw material prices, while the selling price of their products tends to remain, so that the welfare of the tahu tempe craftsmen in DKI Jakarta, is difficult to increase. This also happened to tahu tempe craftsmen in Tahu Tempe Village in Semanan, West Jakarta. This study aims to improve the ability of tahu tempe craftsmen in Semanan by providing a research and development place for tahu and tempe products, marketing assistance and an educational place for related communities, in addition to being able to provide a place for social interaction for local communities from a variety of social, economic and cultural backgrounds to form a community that has character, united and sustainable. As the third place in Semanan, the site was chosen between the residential neighborhood (first place) and the agriculture, industrial, and trade area (second place) with easy accessibility of the two regions. The design method refers to the Responses to Site approach, with the processing of the design prioritizing the principle of porosity which is one aspect of open architecture. This study resulted in concept and design of the third place building with three main facilities, namely community center consisting of a communal space for socializing and interacting visitors and a food research and development kitchen for a means of innovating and developing food products from tempe and tofu, public outdoor space that is used for playing activities, exercising and organizing various events, as well as food market that sells tempe and tahu based foods. Keywords: craftsmen; inovation; porosity; tahu tempe AbstrakMeskipun tingkat konsumsi tahu tempe sangat tinggi, dan Indonesia saat ini menjadi negara produsen tahu dan tempe terbesar di dunia, namun para pengrajin tahu tempe masih mengalami permasalahan dengan harga bahan baku kedelai yang fluktuatif, sementara harga jual produknya cenderung tetap, sehingga kesejahteraan para pengrajin tahu tempe di DKI Jakarta, sulit meningkat. Hal ini juga terjadi di Perkampungan Pengrajin Tahu Tempe di Semanan, Jakarta Barat. Studi ini bertujuan untuk meningkatkan kemampuan pengrajin tahu tempe di Semanan melalui penyediaan wadah riset pengembangan dan inovasi produk olahan tempe dan tahu, bantuan pemasaran dan wadah edukasi bagi komunitas terkait, di samping dapat menyediakan wadah interaksi sosial bagi masyarakat lokal dari berbagai macam latar belakang sosial, ekonomi, dan budaya agar terbentuk komunitas yang berkarakter, menyatu dan berkelanjutan. Sebagai third place, tapak yang akan menjadi kasus studi ini berada di antara kawasan perumahan (first place) dan kawasan pertanian, industri, dan perdagangan (second place) dengan aksesibilitas yang mudah dari kedua kawasan tersebut. Metode desain mengacu pada pendekatan Responses to Site, dengan pengolahan desainnya mengutamakan prinsip porositas yang menjadi salah satu aspek dalam open architecture. Studi ini menghasilkan konsep dan perancangan bangunan third place dengan tiga fasilitas utama, yaitu community center yang terdiri dari ruang komunal untuk bersosialisasi dan berinteraksi pengunjung dan dapur food research and development untuk sarana berinovasi dan pengembangan produk makanan dari tempe, ruang terbuka publik yang difungsikan untuk kegiatan bermain, berolahraga dan penyelenggaraan berbagai event, serta food market yang menjual makanan berbasis tempe dan tahu.